Drug-loaded mucoadhesive microneedle patch for the treatment of oral submucous fibrosis - Cheng, Xian; Yang, Yanqing; Liao, Zhengwei; Yi, Qiao; Zhou, Yueying; Dai, Xiaohan; Liu, Yanping; Liu, Ousheng (Frontiers in Bioengineering and Biotechnology, 2023)
Oral submucous fibrosis is a chronic, inflammatory and potentially malignant oral disease. Local delivery of triamcinolone to lesion site is a commonly used therapy. The existing methods for local drug delivery include topical administration and submucosal injection. However, in the wet and dynamic oral microenvironment, these methods have drawbacks such as limited drug delivery efficiency and injection pain. Therefore, it is urgently needed to develop an alternative local drug delivery system with high efficiency and painlessness. Inspired by the structure of band-aid, this study proposed a novel double-layered mucoadhesive microneedle patch for transmucosal drug delivery. The patch consisted of a mucoadhesive silk fibroin/tannic acid top-layer and a silk fibroin microneedle under-layer. When applying the annealing condition for the medium content of β-sheets of silk fibroin, the microneedles in under-layer displayed both superior morphology and mechanical property. The mechanical strength of per needle (0.071N) was sufficient to penetrate the oral mucosa. Sequentially, the gelation efficiency of silk fibroin and tannic acid in top-layer was maximized as the weight ratio of tannic acid to silk fibroin reached 5:1. Moreover, in vitro results demonstrated the double-layered patch possessed undetectable cytotoxicity. The sustained release of triamcinolone was observed from the double-layered patch for at least 7 days. Furthermore, compared with other commercial buccal patches, the double-layered patch exhibited an enhanced wet adhesion strength of 37.74 kPa. In addition, ex vivo mucosal tissue penetration experiment confirmed that the double-layered patch could reach the lamina propria, ensuring effective drug delivery to the lesion site of oral submucous fibrosis. These results illustrate the promising potential of the drug-loaded mucoadhesive microneedle patch for the treatment of oral submucous fibrosis.